Air movement, gender and risk of sick building headache among employees in a Jakarta office (Medical Journal of Indonesia, 2003)
Even though office buildings are usually equipped with ventilation system or air conditioning to create a comfortable working environment, yet there is still found a number of sick building syndrome (SBS) symptoms. One of the symptoms of SBS is SBS headache. Therefore, it is crucial to identify risk factors related to SBS headache. Cases were subjects who have suffered SBS headache, and controls were subjects who did not suffered headache for the last one month. Cases and controls were selected through a survey on all of employees in the said office during the period of May to August 2002. Total respondents were 240 employees including 36 people suffered SBS headache (15%). Compared to the normal air movement, faster air movement decreased the risk of SBS headache by 57% [adjusted odds ratio (OR) = 0.43; 95% confidence intervals (CI): 0.19-0.95]. Female employees, compared to the males ones, had a higher risk of getting SBS headache by almost three times (adjusted OR = 2.96: 95% CI: 1.29-6.75). Employees who had breakfast irregularly, had a lower risk to SBS headache than those who have breakfast regularly (adjusted OR=0.31; 95% CI: 0.09-0.84). Temperature, humidity and smoking habits were not noted correlated to SBS headache. Female workers had greater risk of suffering SBS headache. In addition slower air movement increased the risk of SBS headache. Therefore, it is recommended to improve the progress of air in order to reduce the risk of SBS headache, especially for female workplace. (Med J Indones 2003; 12: 171-7)